Preparo de compostos de inclusão de hidroclorotiazida, pioglitazona e claritromicina em ciclodextrinas por diferentes técnicas: caracterização e estudos biológicos - Maria Arlete Silva Pires (2011)
Medicine is a pharmaceutical product with prophylactic, curative, palliative or diagnostic purposes. It is necessary to know its physical and chemical characteristics in order to establish its self-assurance and effectiveness. Among these characteristics, the dissolutionrate is a limiting step for the drug absorption. Currently, about 33% of marketed drugs have problems of dissolution. The pharmaceutical industry uses strategies to increase the solubility of drugs and hence its rate of dissolution and bioavailability. One strategy is the useof cyclodextrins, a class of pharmaceutical excipients that is economically and technically viable. This study aimed to obtain inclusion compounds with different techniques for the hydrochlorothiazide (HTZ), pioglitazone hydrochloride (PIO) and clarithromycin (CLA) in order to increase the solubility and the bioavailability of these drugs. The inclusioncompounds were characterized by thermal analysis, infrared spectroscopy, X-ray diffraction powder, scanning electron microscopy, particle size analysis, dissolution studies, nuclear magnetic resonance and were evaluated for in vitro antimicrobial activity (CLA:CD) and invivo diuretic activity (HTZ:CD). The results obtained for the prepared inclusion compounds with the three drugs confirmed and determined host-guest interactions. HTZ formed inclusion compounds with CD in a 1:1 molar ratio, and the results showed that the method of fluidbed by atomization was promising. Results in vivo of diuretic activity showed greater activity for the inclusion compound when compared to free drug. This result was supported by the results of intrinsic dissolution, since the compounds showed greater solubility whencompared with the free drug. PIO formed inclusion compounds in the molar ratio of 1:1 with -cyclodextrin and HP-cyclodextrin. They had much higher solubility than PIO free. Increased solubility can be attributed to the inclusion phenomena and also to the process ofamorphization promoted by spray drying technique. CLA formed a compound in molar ratio of 1:1 and 1:4 and the results of thermal analysis showed that the freeze-drying technique was more effective. However the dissolution studies in buffer showed very similar solubilityprofiles for the compounds obtained, regardless of the technique used. In vitro results of antimicrobial activity against Staphylococcus aureus showed a significant increase in antimicrobial activity of included clarithromycin included when compared with free drug.Therefore, cyclodextrins play a key role on the increasing of the solubility of drugs as well as on the improving of the diuretic and antimicrobial activities of HTZ and CLA, respectively.